Histological Study on the Fibrous Architecture of the Adrenal Gland During Postnatal Development in Buffalo - Kumar, Vishnudeo; Sethi, Ram Saran; Singh, Opinder (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted on the adrenal glands of 29 buffaloes ranging from day old to one year of age. The adrenal gland was fully differentiated into cortex and medulla in the day old buffalo calf and was completely surrounded by a dense fibrous capsule at this stage. The capsule consisted of outer layer of loose connective tissue and inner layer of thick collagen fibres. The connective tissue trabeculae made up of collagen and reticular fibres arose from the inner aspect of capsule and infiltrated the cortical parenchyma of the gland. The reticular fibres dominated in the inner aspect of the capsule and the proportion of reticular fibres was more in the zona glomerulosa and outer zone of medulla, however, elastic fibres were not observed in any part of the gland up to one year of age. The average thickness of the capsule increased with progression of age which was due to increase in the density of collagen fibres especially in the inner zone of capsule.